2020
DOI: 10.1371/journal.pone.0230147
|View full text |Cite
|
Sign up to set email alerts
|

Does endo-tracheal tube clamping prevent air leaks and maintain positive end-expiratory pressure during the switching of a ventilator in a patient in an intensive care unit? A bench study

Abstract: ObjectivesWhen patients with acute respiratory distress syndrome are moved out of an intensive care unit, the ventilator often requires changing. This procedure suppresses positive end expiratory pressure and promotes lung derecruitment. Clamping the endotracheal tube may prevent this from occurring. Whether or not such clamping maintains positive end-expiratory pressure has never been investigated. We designed a bench study to explore this further. How the study was doneWe used the Elysee 350 ventilator in 'v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…Their results showed that the extracorporeal membrane oxygenation (ECMO) clamp had the best performance in preventing leak (volume loss) after circuit disconnection. The leakage results were ECMO clamp (15ml/5s; 20ml/30s), metal clamp (113ml/5s; 423ml/30s) and plastic clam (693ml/5s; 692ml/30s) respectively [ 104 ].…”
Section: Prudently Applying Non-invasive Respiratory Support (Nirs)mentioning
confidence: 99%
“…Their results showed that the extracorporeal membrane oxygenation (ECMO) clamp had the best performance in preventing leak (volume loss) after circuit disconnection. The leakage results were ECMO clamp (15ml/5s; 20ml/30s), metal clamp (113ml/5s; 423ml/30s) and plastic clam (693ml/5s; 692ml/30s) respectively [ 104 ].…”
Section: Prudently Applying Non-invasive Respiratory Support (Nirs)mentioning
confidence: 99%
“…When transporting a mechanically ventilated COVID-19 patient, it is suggested that a filter HME be placed between the artificial airway and the transport ventilator circuit [ 53 ]. Before pausing the ICU ventilator, consider clamping the endotracheal tube (ETT) to prevent derecruitment and minimize the spread of bio-aerosols when transitioning patients from the ICU ventilator to the transport ventilator [ 5 , 87 , 88 ]. When returning to the ICU, clamp the ETT and leave the filter connected to it to prevent accidental exposure.…”
Section: Literature Findings and Suggestionsmentioning
confidence: 99%
“…In order to minimize the risk, closed circuit endotracheal suctioning was used. Endo-tracheal tube clamping was realized with ECMO clamps (18) during the installation of the device, which requires disconnection and reconnection from the ventilatory circuit. According to Sedana Medical, the virus filtration capacity of AnaConDa is superior to 99.9% for 27 nm particles, which corresponds to less than a quarter of the SARS-CoV-2 virus size (120-160mm) (19).…”
Section: Discussionmentioning
confidence: 99%